Pengembangan E-LKPD Interaktif Berbasis Liveworksheet Pada Materi Volume Bangun Ruang - Taupik, Baban; Ruhiat, Yayat; Rusdiyani, Isti (Prodi Pendidikan Matematika Universitas Pesantren Tinggi Darul Ulum Jombang, 2024)
This development research is a form of teaching media innovation on multimedia-based Student Worksheets assisted by the Live worksheet application. Development research was carried out using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) aims to increase enthusiasm for learning and learning outcomes in students. Observations, interviews, and questionnaires it used to collect qualitative and quantitative data. In addition, the validation test of this study involved material experts, media experts, and educator practitioners. From the results of the material validation, an average of 4.6 or 92% and the results of the media validation were an average of 4.4 or 88%, and the product test results from practitioners obtained 82.5%. Based on the results of the average acquisition, the e-LKPD is very feasible to try out, and the test results from students get a good response of 86%. So that concluded that the e-LKPD development product based on Live worksheet Material Build Volume Class V Elementary Schools is suitable for use as teaching material in learning for students.